2014
DOI: 10.1186/1471-2407-14-205
|View full text |Cite
|
Sign up to set email alerts
|

The pemetrexed-containing treatments in the non-small cell lung cancer, is -/low thymidylate synthase expression better than +/high thymidylate synthase expression: a meta-analysis

Abstract: BackgroundThe predictive value of thymidylate synthase (TS) for clinical sensitivity to pemetrexed-containing chemotherapy in patients with non-small cell lung cancer (NSCLC) remains controversial. This meta-analysis is performed to provide an assessment of whether expression variations of TS are associated with objective response in patients with NSCLC treated with pemetrexed-containing chemotherapy.MethodsAn electronic search was conducted using the databases MEDLINE, EMBASE and CNKI, from inception to June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…12 The low expression rate of ERCC1, RRM1, TS and β-tubulin III, and the PD-L1 positive rate, differing from other studies, might be due to, for instance, different races, proportions of histology and stages. [13][14][15] In particular, the issue of ERCC1 isoform and PD-L1 antibody selection for IHC is worth mentioning. Friboulet et al 16 detected and elaborated on the function of ERCC1 isoform 202 for nucleotide excision repair and cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…12 The low expression rate of ERCC1, RRM1, TS and β-tubulin III, and the PD-L1 positive rate, differing from other studies, might be due to, for instance, different races, proportions of histology and stages. [13][14][15] In particular, the issue of ERCC1 isoform and PD-L1 antibody selection for IHC is worth mentioning. Friboulet et al 16 detected and elaborated on the function of ERCC1 isoform 202 for nucleotide excision repair and cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Low level of TS expression has been considered a favorable marker for the efficacy of pemetrexed in NSCLC 33,35 and lung adenocarcinoma. 34 Our findings showed a very low TS level (median TS H-score of 55) in lung adenocarcinomas, which was similar to that in a previous report.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] Interestingly, novel ROS1 fusion-positive tumors, which share similar clinical characteristics with ALK fusion tumors, 30 were also recently reported as having longer PFS and higher response rates. 16,[31][32] Although prior reports suggested that TS expression levels were inversely correlated with the response to pemetrexedbased chemotherapy in NSCLC, [33][34][35] the correlation of TS expression level with the length of response during pemetrexed chemotherapy is still controversial in NSCLC tumors with different molecular alterations (e.g., EGFR mutation, EML4-ALK fusion, ROS1 fusion, and wild type). 24,26,27,31 The interaction between these driver mutations and the duration of pemetrexed-associated benefits has recently attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…To optimally balance the number of patients in the subgroups, due to the small sample size and 2:1 randomization, the cutoff point for low versus high TS expression was the median H score for the study population evaluable for TS. 32 Treatment-emergent adverse events (AEs) were reported according to the Medical Dictionary for Regulatory Activities (version 18.0) and graded using the National Cancer Institute Common Terminology Criteria for Adverse Events (version 4.0).…”
Section: Assessments and Statistical Analysesmentioning
confidence: 99%